Influence of carbon source, pH, and temperature on the polygalacturonase activity of Kluyveromyces marxianus CCMB 322 - Rodrigo de Queiroz OLIVEIRA (Ciência e Tecnologia de Alimentos, 2012)
Microbial pectinolytic enzymes are known to play a commercially important role in a number of industrial processes. Two kinds of yeast can be discerned regarding the production of enzymes. One group includes those which can produce enzymes in the absence of an inducer, and the other group comprises the yeasts that produce enzymes in the presence of an inducer. The objective of this study was to investigate the influence of pectic substances, glucose, pH, and temperature on the polygalacturonase activity by Kluyveromyces marxianus CCMB 322. The yeast was grown in a fermentation broth containing different concentrations of glucose and pectic substances. The polygalacturonase activity was determined by the DNS method, and the pH and temperature were optimized using a central composite experimental design. The polygalacturonase secreted by K. marxianus CCMB 322 was partially constitutive showing optimum pH and temperature of 7.36 and 70 °C, respectively, and maintained approximately 93% of its original activity for 50 minutes at 50 °C. Thermal stability of the polygalacturonase enzyme was studied at different temperatures (50, 60, 70, and 80 °C) and different incubation times (0, 10, 20, 30, 40, and 50 minutes). This study showed that glucose can influence the regulation of the synthesis of polygalacturonase.